The effect of foodborne sertraline on rainbow trout (Oncorhynchus mykiss) - Vaclavik, Josef; Sehonova, Pavla; Hodkovicova, Nikola; Vecerkova, Lenka; Blahova, Jana; Franc, Ales; Marsalek, Petr; Mares, Jan; Tichy, Frantisek; Svobodova, Zdenka; Faggio, Caterina (The Science of the total environment, 2020)
The worldwide consumption of antidepressants is raising as well as their concentrations in the aquatic environment. This increases the risk of food chain contamination and bioaccumulation in aquatic biota. The aim of this study was to describe a potential risk of sertraline as a pollutant from water environment, wherein rainbow trout (Oncorhynchus mykiss) has been chosen as the test organism, because predatory fish are on the top of the food chain in the aquatic environment. The effects of foodborne sertraline were tested on rainbow trout during a 28-day toxicity test according to OECD 215 method. Sertraline was incorporated in commercial feed at a dose of 4.4 µg/kg (environmental concentration), 42 µg/kg and 400 µg/kg. The results confirmed that sertraline has a significant effect on fish behaviour, resulting in suppression of the escape reflex and increased resistance to stress. Moreover, increased Fultońs condition factor was found in fish fed with the highest concentration of sertraline. Haematological analysis revealed a statistically significant increase in the number of neutrophilic bands and neutrophil/lymphocyte ratio, and decreased number of lymphocytes. The results of biochemical examination showed a statistically significant decrease in ammonia and lactate concentrations and histological examination revealed changes in gills and caudal kidney. Although sertraline reduces stress in fish, the decline in nonspecific immunity is a risk to fish population stability.
Keywords: Animals; Fish; Ammonia; Haematological profile; Oncorhynchus mykiss; Gills; zvířata; Oxidative stress; látky znečišťující životní prostředí; Behaviour; amoniak; žábry; Environmental Pollutants; Sertraline; sertralin; Antidepressant